Avaliação dos projetos de P&D da CHESF - Inácio, Edmundo; Garcia Ribeiro, Cassio [UNESP]; Furtado, André T.; Sicsú, Abraham; Távora, Luciana; Silva, Gabriela; Guedes, Valencio P. (My University, 2014)
The purpose of this article is to present the proposed methodology created and applied to evaluate the R&D project of the CHESF. Based on interactive innovation model, the proposed methodology relies primarily on documentary research and a survey. Adopting more of a tool to evaluate the R&D projects, allowed the construction of a more comprehensive picture of the CHESF innovation process. The methodology has been successfully tested and proved an important tool for evaluating policies to promote R&D.
Evaluation of R&D projects CHESF
Keywords: R&D Valuation; Technological and innovation policy; The brazilian electricity sector